10.1016/s1544-8800(08)70215-x (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: The School Breakfast Program (SBP) provides academic and nutritional benefits to U.S. children. In Utah, the Start Smart Utah policy requires schools with higher proportions of students from low-income backgrounds to adopt alternative breakfast models. Research suggests policy adoption does not guarantee effective implementation. This study examined school stakeholders' perspectives on implementing Start Smart Utah. METHODS: This qualitative study recruited Utah school stakeholders (n = 32) whose schools were required to implement an alternative breakfast model under Start Smart Utah. A semi-structured interview guide explored implementation experiences and perceived support. Interviews were analyzed using reliability thematic analysis. RESULTS: Five themes were constructed: (a) supporting students through school breakfast, (b) initial implementation: shifting strategies and support, (c) student participation in school breakfast, (d) tensions among quality, choice, and waste, and (e) recommendations for strengthening alternative breakfast models. IMPLICATIONS FOR SCHOOL HEALTH POLICY, PRACTICE, AND EQUITY: Findings show that clear communication, adequate resources, and stakeholder engagement are essential for policy success. Embedding funding, training, and feedback mechanisms can improve implementation and equity. CONCLUSIONS: SBPs remain vital to student well-being and academic success. Start Smart Utah shows that expanding access through policy can yield benefits, but success depends on implementation realities.